INCREASING TEACHERS' CAPABILITIES IN DISTANCE LEARNING USING THE GOOGLE CLASSROOM APPLICATION THROUGH PERSONAL ASSISTANCE OF TEACHERS IN KEMPONG KALIBAWANG, KULON PROGO DISTRICT, 2020/2021 - Dwi Wahyuni (Universitas Islam Indonesia, 2021)
This research is motivated by teachers who are still not ready to face distance learning during the Covid-19 pandemic. To overcome this problem researchers take corrective actions through school action research which aims to improve the ability of teachers and researchers to provide personal assistance using the Google Classroom application program for learning. distance and improve school performance in order to be able to compete in the field of graduation. The research design uses a qualitative design, while the data collection technique uses the method of documentation and observation. The data analysis technique was carried out through a qualitative descriptive model consisting of data reduction, data presentation, and drawing conclusions. The results of this study can be seen from the increase in the results of the ability of the participants in personal assistance and the implementation of activities by resource persons from before the action in cycles I and II. In the pre-cycle of participants who got an average score of 3.52, the percentage was 88.04% with the